Teatr w Zielonej Górze między zakończeniem II wojny światowej a inauguracją sceny publicznej = Theater in Zielona Góra between the end of World War II and the inauguration of the public stage - Michalak, Hubert (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article is focused on theatrical activity in Zielona Góra between 1945 and 1951. It covers non-professional activities, an early attempt to launch a public stage and Róża Gella-Czerska`s successful work.
Keywords: Zielona Góra; teatr; Gella?Czerska, Róża (1891-?); inauguracja teatru; theatre; theater inauguration